ALUR KERJA SISTEM INFORMASI MANAJEMEN (SIM) “LESTARI” PADA PELAYANAN SANITASI DI KABUPATEN SIDOARJO - Xenya Novita Wijayati (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Digitalization in public services is a strategic step to realize transparent and accountable governance. This study aims to describe the utilization workflow of the 'Lestari' Management Information System (MIS) within the administrative procedures for septic tank desludging services at the UPTD PALD of Sidoarjo Regency. Employing a qualitative method with a case study approach, this research maps the information system cycle (input-process-output) operating within the system. The results indicate that Lestari successfully functions as a reliable regional sanitation data center, where the system is capable of managing the database with the active assistance of officers. The system's strength is significantly evident at the output stage, where the implementation of barcode technology and a multi-level scanning mechanism ensures transparency in field task execution and compliance with waste disposal. This study concludes that the combination of meticulous manual verification and digital system validation has created administratively orderly and controlled sanitation services.